2021
DOI: 10.3389/fimmu.2021.664845
|View full text |Cite
|
Sign up to set email alerts
|

CD2 Is a Novel Immune-Related Prognostic Biomarker of Invasive Breast Carcinoma That Modulates the Tumor Microenvironment

Abstract: Female breast cancer (BCa) is the most commonly occurring cancer worldwide. The tumor microenvironment (TME) plays an essential role in tumor invasion, angiogenesis, unlimited proliferation, and even immune escape, but we know little about the TME of BCa. In this study, we aimed to find a TME-related biomarker for BCa, especially for invasive breast carcinoma (BRCA), that could predict prognosis and immunotherapy efficacy. Based on RNA-seq transcriptome data and the clinical characteristics of 1222 samples (11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 39 publications
5
33
0
Order By: Relevance
“…The intersecting genes between the prognostic genes and the hub genes were CD2 and CD40LG ( Figure 4C ). Because CD2 had been a known prognostic genes in BRCA, 12 , 14 we herein focused on CD40LG for further investigation.
Figure 4 Core prognostic genes analysis.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intersecting genes between the prognostic genes and the hub genes were CD2 and CD40LG ( Figure 4C ). Because CD2 had been a known prognostic genes in BRCA, 12 , 14 we herein focused on CD40LG for further investigation.
Figure 4 Core prognostic genes analysis.
…”
Section: Resultsmentioning
confidence: 99%
“… 11 In addition, Chen et al and Wang et al respectively revealed that CD2 and CD52 were two immune-related prognostic factor in BRCA via regulating TME. 12 , 13 With similar approach, we identified another prognostic gene that was deeply involved in the immune and TME regulation of BRCA through an integrated bioinformatic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, CD2 was considered a prognostic biomarker in a previous study due to the strong correlation with OS. The possible reason for this contradiction may be that they did not consider the clinical factors ( 20 ). In addition, the BC samples were grouped into ITK high-expression and low-expression groups compared with the ITK median expression.…”
Section: Discussionmentioning
confidence: 99%
“…Common and important immune cells include neutrophils, natural killer cells, macrophages, dendritic cells, B cells, and T cells. In the TME, various immune factors are regulated by various key factors while playing their roles (58)(59)(60). Moreover, an increasing number of studies have shown that immune cells play important roles in the occurrence and development of many tumors (61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%